The Relationship between Hostile Attribution and Divorce Proneness: Investigating the Mediating Role of Self-Differentiation in Women - Yadegari , Seyedeh Liba; Peyvandi, Parisa; Hosseinzadeh Taghvaei , Marjan; Beliad , Mohammadreza; Mahmoodinia , Saeed (Advances in Nursing & Midwifery, 2025)
Introduction: Hostile attribution, interpreting a partner’s ambiguous actions as malicious, significantly contributes to marital conflict by perpetuating negative interaction cycles and eroding trust. This investigation aimed to explore the association between hostile attribution and divorce proneness in women, specifically examining the mediating influence of self-differentiation. Methods: This study adopted a cross-sectional correlational design. Data were gathered from a convenience sample of 350 married women residing in Karaj, Iran, during 2024. Participants completed a battery of standardized self-report measures, specifically the Hostile Attribution Scale, the differentiation of Self Inventory, and the Divorce Propensity Questionnaire. The collected data underwent statistical analysis using Structural Equation Modeling (SEM) to thoroughly assess the hypothesized direct and indirect relationships among the variables. Results: Findings indicated a significant positive correlation between hostile attribution and divorce proneness (r=0.40, P<0.001). Additionally, hostile attribution was negatively correlated with self-differentiation (r=-0.30, P<0.001). Furthermore, self-differentiation was negatively correlated with divorce proneness (r=-0.50, P<0.001). Crucially, self-differentiation emerged as a statistically significant mediator in the relationship between hostile attribution and divorce proneness. The structural model demonstrated good fit (χ²/df=1.78, CFI=0.94, RMSEA=0.045). Conclusions: These results suggest that hostile attribution contributes to a diminished capacity for self-differentiation, which, in turn, increases a woman’s predisposition to divorce. Understanding this psychological pathway is vital for developing targeted interventions aimed at fostering healthier relational cognitions and enhancing marital resilience.